Comparison of cytomorphology and histomorphology in myelodysplastic syndromes - Nachtkamp, Kathrin; Strupp, Corinna; Faoro, Rosa; Gattermann, Norbert; Dietrich, Sascha; Germing, Ulrich; Baldus, Stefan (Frontiers in Oncology, 2024)
Gold standard for the establishment of the diagnosis of myelodysplastic syndromes are cytomorphological features of hematopoietic cells in peripheral blood and bone marrow aspirates. There is increasing evidence that bone marrow histomorphology not only aids in the diagnosis of MDS but can provide additional prognostic information, particularly through assessment of fibrosis and cellularity. However, there is only sparse data on direct comparison between histological and cytomorphological findings within the same MDS patient cohort. cytomorphological diagnosis. The latter, likewise, was uniformly made by the same expert cytomorphologist (U.G.).Assignment to the diagnostic WHO subgroup was not entirely concordant with cytomorphology, mainly due to incongruences between the proportion of CD34-positive cells on histopathology and the cytomorphological blast count. Histopathology provided additional diagnostic and prognostic information with high diagnostic and prognostic significance, such as fibrosis. Likewise, histopathology allowed more reliable estimation of bone marrow cellularity.